Synthesis, characterization and stress-testing of a robust quillaja saponin stabilized oil-in-water phytocannabinoid nanoemulsion - Abhinandan Banerjee; Justin Binder; Rayan Salama; John F. Trant (BMC, 2021)
Abstract Background This study describes the design, optimization, and stress-testing of a novel phytocannabinoid nanoemulsion generated using high-pressure homogenization. QNaturale Ⓡ $\text {QNaturale}^{\circledR }$ , a plant-derived commercial emulsifier containing quillaja saponin, was used to stabilize the lipid phase droplets in water. Stress-testing was performed on this nanoemulsion in order to evaluate its chemical and colloidal stability under the influence of different environmental factors, encompassing both physical and chemical stressors. Methods Extensive optimization studies were conducted to arrive at an ideal nanoemulsion formulation. A coarse emulsion containing 16.6 wt% CBD-enriched cannabis distillate and 83.4 wt% carrier (soybean) oil dispersed in 10 wt% QNaturale Ⓡ $\text {QNaturale}^{\circledR }$ (1.5 wt% quillaja saponin) solution after 10 homogenization cycles at a pressure of 30,000 psi produced a stable nanoemulsion. This nanoemulsion was then subjected to the stress studies. Results The optimized nanoemulsion had an average droplet diameter of ca. 120 nm and average droplet surface ζ potentials of ca. -30 mV. It was imaged and characterized by a variety of protocols. It proved to be stable to droplet agglomeration and phase separation upon storage under ambient conditions for 6 weeks, as well as under a variety of physical stressors such as heat, cold, dilution, and carbonation. pH values ≤2 and moderately high salt concentrations (> 100 mM), however, destabilized the nanoemulsion, eventually leading to phase separation. Cannabis potency, determined by HPLC, was detrimentally affected by any changes in the nanoemulsion phase stability. Conclusions Quillaja saponin stabilized cannabidiol(CBD)-enriched nanoemulsions are stable, robust systems even at low emulsifier concentrations, and are therefore significant from both a scientific as well as a commercial perspective.